Effects of Syngenta Enogen Feed Corn containing an α-amylase trait on finishing cattle performance and carcass characteristics() - Jolly-Breithaupt, M L (Transl Anim Sci, 2018)
Two experiments evaluated the effects of feeding a new corn hybrid, containing an α-amylase enzyme trait, Syngenta Enogen Feed Corn (SYT-EFC), on feedlot performance and carcass characteristics at two locations. Experiment 1 utilized 300 calffed steers (298.5 ± 16.3 kg of BW) at the University of Nebraska–Lincoln Eastern Nebraska Research and Extension Center Mead, NE. Treatments were designed as a 2 × 2 + 1–factorial arrangement with factors consisting of 1) corn type (SYT-EFC or conventional [CON]) and 2) byproduct type (with or without Sweet Bran [SB]), or a BLEND of STY-EFC and CON without SB. In Exp. 2, 240 crossbred, calf-fed steers (287.6 ± 15.4 kg of BW) were utilized at the University of Nebraska–Lincoln Panhandle Research and Extension Center near Scottsbluff, NE. Steers were fed SYT-EFC, CON, BLEND, or CON with a commercial α-amylase enzyme supplement (CON-E). In Exp. 1, there was an interaction for ADG (P = 0.05) and G:F (P = 0.02). Steers fed SYT-EFC with SB had greater ADG and G:F than CON; however, in diets without SB, SYT-EFC and CON were not different resulting in a 10.1% change in G:F when steers were fed SYT-EFC in SB compared with CON and only 1.6% change between SYT-EFC and CON without SB. Energy values, based on performance data, resulted in a 6.5% and 8.3% change in NE(m) and NE(g), respectively, for steers fed SYT-EFC and CON with SB and 1.6% change for both NE(m) and NE(g) for steers fed SYT-EFC and CON without SB. For the main effect of corn trait, steers fed SYT-EFC had greater marbling scores, fat depth, and calculated yield grade compared with CON (P ≤ 0.03). In diets without SB, there was no difference between SYT-EFC, CON, or BLEND for DMI, final BW, ADG, G:F, NEm, or NEg (P ≥ 0.35). In Exp. 2, cattle fed SYT-EFC, BLEND, or CON-E had greater final BW, ADG, and G:F than cattle fed CON (P ≤ 0.03). On average, NE(m) and NE(g) were 4.9% and 7.0% greater, respectively, for steers fed amylase enzyme treatments compared with CON (P ≤ 0.01). Hot carcass weights were greater in steers fed α-amylase treatments compared with CON (P < 0.01). Feeding Syngenta Enogen Feed Corn, which contains an α-amylase enzyme trait, at both locations improved feed efficiency in finishing cattle diets containing WDGS or SB.